Two new genera of Sclerodermini (Hymenoptera: Bethylidae; Epyrinae) with large, scolebythid-like prosternums - Azevedo, C. O. (Zootaxa, 2006)
The following new taxa are proposed, described and illustrated: Megaprosternum gen. nov. including M. longiceps sp. nov. from Fiji and M. pentagonal sp. nov. from Australia; and Solepyris gen. nov. including S. unicus sp. nov. from Brazil and Ecuador. Keys are provided for the genera of Sclerodermini and for the species of Megaprosternum .